(untitled) (Training and Practice : Journal of Educational Sciences, 2021)
Dictionaries have long been recognised as an essential learning resource. We can find many specialised and user-friendly dictionaries in the market. Problems may arise when teachers and learners do not know how to use these materials to assist learning. This paper shows how dictionary skills can be integrated into the English syllabus and taught explicitly in class. In this way, teachers will be able to play an important role in building a bridge between lexicographers and unskilled learners.